Child labor and conflict: Evidence from Afghanistan - Chiara Kofol; Tommaso Ciarli (University of Bonn, Center for Development Research (ZEF), 2017)
We study the impact of conflict on both the extensive and the intensive margin of child labor in Afghanistan. We identify and test two main mechanisms. First, if conflict reduces a household income through a decline in parent's compensations, child labor may insure against the decrease in consumption (extensive margin). Second, a child may work longer hours if the marginal benefits of working under conflict is greater than its marginal cost, which may depend on the relative compensations between adults and children, and on the alternative activities (e.g. schooling). Using detailed conflict data from the Afghan War Diary we identify the effect of conflict relying on a shift-share IV strategy. We find that conflict increases the probability that girls work, but reduces the number of hours worked. Our results suggest that this is due to a decrease in household income and an increase in the relative compensations of adults.
Keywords: J13; D74; 330; Afghanistan; child labor; school attendance; conflict